Transfusion rates after 800 Aquablation procedures using various haemostasis methods. (24th January 2020) - Elterman, Dean; Bach, Thorsten; Rijo, Enrique; Misrai, Vincent; Anderson, Paul; Zorn, Kevin C.; Bhojani, Naeem; El Hajj, Albert; Chughtai, Bilal; Desai, Mihir
Abstract : Objective: To determine if athermal methods are as effective in preventing blood transfusions as the use of cautery across various prostate volumes following prostate tissue resection for benign prostatic hyperplasia using Aquablation. Patients and methods: The current commercial AQUABEAM robot that performs Aquablation therapy was first used in 2014. Since then numerous clinical studies have been conducted in various countries; Australia, Canada, Germany, India, Lebanon, Spain, New Zealand, United Kingdom, and the United States. All of the clinical trial data since 2014 were pooled with the early commercial procedures from France, Germany, and Spain to determine the effectiveness of haemostatic techniques in reducing the transfusion rate in patients after Aquablation. Results: In all, 801 patients were treated with Aquablation therapy from 2014 to early 2019. The mean (SD, range) prostate volume was 67 (33, 20–280) mL and 31 (3.9%) transfusions were reported. The largest contributing factor to transfusion risk was prostate size and method of traction. There was an increasing risk of transfusions in larger prostates when robust traction using a catheter‐tensioning device (CTD) without cautery was used, ranging from 0.8% to 7.8% in prostates ranging from 20 to 280 mL. However, when standard traction (taping the catheter to the leg, gauze knot synched up to the meatus, or no traction at all) was used and where the surgeon performed bladder neck cautery only when necessary, the risk of transfusion was 1.4–2.5% in prostates ranging from 20 to 280 mL. Conclusions: While the athermal subgroup with robust traction with a CTD had comparable transfusion rates for smaller prostates, the risk increased significantly as prostate volume increased. With standard traction methods and selective bladder neck cautery, the risk of transfusion was reduced to 1.9% across all prostate sizes.